المعلم الناجح ودوره في تنمية الموارد البشرية - جدوع محمد, عبد الرزاق; حسين يحيى, داليا (Journal of College of Education, 2020)
If the preparation and development of human resources is the responsibility of multiple societal institutions, then education (the responsibility of the teacher as the basis of the educational process) is the primary tool for society in performing these jobs, and the episodes of this educational system begin from the kindergarten stage which children join between 4- 5 years . However, the quantitative growth and educational development in these institutions is very limited and pay attention to their importance only in the past few years.The reality is that childhood development and its physical, intellectual and psychological development represent the basis for human resource development, and despite the widespread interest shown in its issues in the past years, childhood has not received sufficient priority yet. It is necessary that the fulfillment of basic childhood needs, including education and pre-primary school, be considered a national priority in the Arab development integration and human resource development plan.The teacher is the primary source in the formation of skills and high know-how in the human resource as the most important resource required to bring about development. Therefore, the most important questions that arise in the field of education in general and for basic education in particular is what is the role of the teacher in economic and social development or what happened and happens from growth In the production sectors, providing services and improving the standard of living?Multiple studies have been conducted to highlight the value of investment in human capital through education, and these studies, which were conducted mostly in the United States of America and in the former Soviet Union, demonstrated that the growth in national income during certain periods cannot be explained on the basis of increasing material production factors and increasing Capital, and the conclusion came to the presence of other factors called the residual factor represented in the high level of skill in the workforce and the use of technological applications, and other factors associated with education.Therefore, the teacher is the cornerstone of the educational process, the process that is not straightforward unless the human workforce in its fields is sufficient and secure in the educational message and its value, and the teacher has a conscientious conscience, and the primary function of the teacher is to educate students at all levels and to communicate all that is involved in education operations To their minds and hearts.A successful teacher is the pioneer of the people, and the baptism that can shape society and prepare him for free and decent lifestyles and for this he must be aware of his message believing in it, and must have all the elements that enable him to carry out this honorable message of honesty, knowledge, knowledge, conscience, culture and training , Because the formation of souls, refining minds and caring for bodies is a difficult and arduous process and because it is necessary to build the body, then the teacher’s message is then above all fate and consideration. So the teacher's satisfaction with his work, his production, and the comfort of his conscience was that he performs his duties completely sacrificed for the sake of that all his time and effort in order to nurture his children, these are the essential elements in achieving the free educational mission that is based on the teacher's belief in it and its seriousness in the progress of society, this faith must Its effects on young people and society are reflected in its sacred advance to a better life.Educational institutions in Iraq have faced in the past decades difficult conditions represented by military and economic wars. One of their direct effects was the deterioration of levels of education, both basic and high.Because education is organically linked to other institutions of society, the devastation and devastation caused to it inevitably withdraws on education, as a result of these conditions, including but not limited to the lack of school buildings, the insufficiency of old school buildings to meet the requirements of education, they are unable to accommodate the increasing numbers Among the students, the deterioration of the teacher’s social position, the prevalence of unemployment among most graduates of schools, colleges and institutes, the low level of education, etc.Education also faced at the present time some of the problems that were represented by modern communication technology and its wrongful uses by most of our students, which are (the Internet, mobile phone, and satellite) and others, as our students spend with them the long hours tirelessly, as they did not devote most of their time to reading and completing their homework.All these social conditions that the Iraqi society suffered at the time contributed to the inability of education to prepare and develop human resources, which are the basis for comprehensive development, as comprehensive development is based on education just as education depends on development.We hope that this modest attempt deserves attention as it addresses an educational phenomenon that affects our social reality, especially human development issues, after which the basis of development issues